Strategi Guru dalam Memotivasi Siswa Belajar Bahasa Inggris Online - Lulu Khoerun Nisa; Rahma Ilyas; Titin Kustini (Journal of Language Education (JoLE), 2022)
Abstract Motivation has a very important role in learning. This motivation leds to enthusiams in learning and can improve learning outcomes. This research aims to find out what are the media and strategies that teachers use to motivating students in learning English online. The second aims is to find out how the students involvement in learning English online. This research is descriptive qualitative research. The participants in this research are three of English teachers and three of 10th grade students in SMK PUI Majalengka. The data were collected by observation and interview. The result showed that teachers often using WhatsApp during learning English online. Then, the strategies used by teachers to students motivation for learning English online were reminding the study schedule, giving a games or quizz, giving more interesting materials, and giving Intermezzo. Besides, student involvement in online learning is quite good. Regarding the media used during online learning of English, two students stated that the students not satisfied using WhatsApp, and the students want to use Zoom. Meanwhile, one student stated that satisfied using WhatsApp, but the student want to use E-learning with added video features. However, WhatsApp received a positive response from students. Students stated that WhatsApp made it very easy for them to access materials anytime and anywhere.